What Demotivates EFL Learners - Wu, Yanting; Ding, Feng (International Journal of Linguistics, 2022)
70 university EFL learners of low proficiency were surveyed to investigate the demotivating factors in learning English as a foreign language (EFL) in China, and the ebb and flow of enthusiasm towards English experienced by EFL learners of low proficiency. Findings from this study indicate that less-proficient EFL learners might go through four stages of emotion, from motivated to demotivated, to remotivated, and lastly to relinquish. Burdensome coursework, persistent negative feedback, and disagreeable teachers are the three main factors that affect students’ enthusiasm for learning English. The implications of this study are that it complements the studies of demotivators by examining the causes of less proficient students’ fluctuation of enthusiasm for English in the Chinese context, and further explores the processes by which learners’ enthusiasm for English changes, so that policymakers and administrators can identify and address problematic aspects of educational policies and classroom practices.